Consumption of dairy products in adolescents in Tehran - Elham Feizabad; Zhila Maghbooli; Eghbal Taheri; Bagher Larijani (Shahid Beheshti University of Medical Sciences, 2019)
Background: Dairy products are required for bone metabolism; however, the majority of adolescent do not consume the products adequately. This study was performed to assess the prevalence of dairy products consumption, daily calcium, vitamin D intake, and vitamin D deficiency.   Methods: In this cross-sectional study, 444 females and males' students in middle and secondary school were recruited by using mixed sampling method. Food Frequency Questionnaire (FFQ) was used to estimate dietary calcium and vitamin D consumption. Serum calcium, and 25 (OH) vitamin D were measured. The data was analyzed by IBM SPSS Statistics for Windows, Version 19.0. Armonk, NY: IBM Corp. T-test, Chi2 and Spearman correlations tests were used as well.     Results: Out of all participants, 214 (48.2%) were females. The average age of the participants was 14.34 years and 206 (46.6%) of the students were in middle and 238 (53.6%) were in high school. 409 (92.1%) of the students consumed at least one glass of milk per week. Calcium intake from milk and yoghurt was more than calcium intake from other dairy products. The amount of calcium lower than 700 mg/day was consumed in 176 (39.6%) of adolescents. There was a significant positive correlation between weekly calcium intake and serum vitamin D level (P=0.001). The prevalence of vitamin D deficiency was higher in females rather than males (151 (71.2%) vs. 40 (17.5 %)).    Conclusion: Adolescents in Tehran do not consume dairy products enough. Indeed, encouraging teenagers to consume dairy products and alter in dietary patterns that improve calcium intake, should be taken in to consideration.